(Table 2) Uranium and thorium isotopic composition, activity ratios and ages of bivalvia shells in sediment core GIK14350, northern Germany, supplementary data to: Lomitschka, Michael; Frank, Norbert; Mangini, Augusto (1997): Untersuchungen zur Th/U-Datierung eemzeitlicher Muscheln aus Schleswig-Holstein. Meyniana, 49, 85-102 - Lomitschka, Michael; Frank, Norbert; Mangini, Augusto (PANGAEA - Data Publisher for Earth & Environmental Science, 1997)
A new chemical procedure for cleaning marine carbonates was applied to remove detritus as well as metaloxide contaminations of marine shells from Eemian deposits and adjoining succession of a sediment core from Dagebüll, Schleswig- Holstein. Hence, one can significantly reduce the contamination with detrital uranium and thorium. Thermal ionisation mass spectrometry was applied to determine the uranium and thorium activities used for 230Th/U dating of these shells. At least ten samples of marine bivalves of five different core sections were analysed. Samples located below a five meter thick clay layer at 19-24 m yielded an average age of 132±18 ka. Shells located above the clays at 15-20 m depth were strongly influenced by percolating groundwaters of an open system. Therefore, a reliable dating of these samples was not possible.
This dataset is supplement to doi:10.2312/meyniana.1997.49.85
Keywords: Datensammlung